ANALISIS PENGARUH ROTOR CLEARANCE PADA HIGH PRESSURE COMPRESSOR DAN HIGH PRESSURE TURBINE TERHADAP PENURUNAN EXHAUST GAS TEMPERATURE MARGIN PADA MESIN CFM56-3C1 - Fikri Aulia Izzatur Rahim (Jurnal Teknik Mesin)
The aircraft engine shall always be checked for performance by paying attention to engine parameters and performes maintenance to maintain the condition of the aircraft. The most important parameter of the engine is Exhaust Gas Temperature Margin (EGTM) which is the difference between the maximum temperature limit on the mesin and the actual temperature read at the time of take-off.  On the CFM56-3C1 engine with serial number 856745, a test was carried out to determine the condition of the engine's performance, the results showed that the engine has an EGT Margin -10.9 °C and has decreased by 26.2 °C from the last engine repair. From the results, it is necessary to improve the performance of the EGT Margin engine by carrying out improvements to the workscope performance level, namely improvements to the clearance or distance between the rotor on the High pressure Compressor and the compressor case and the distance of the rotor on the High Pressure Turbine with the turbine shroud/stator which can cause a decrease in the value EGT Margin or called EGT Effect. EGT Effect calculation needs to be done to find out how big the contribution of the rotor clearance mismatch on HPC and HPT to the decrease in EGT value. The Margin affected by rotor clearance can be calculated from the actual clearance measurement minus the maximum clearance size that the factory has set and multiplied by the EGT Effect value per mils/microinch of each stage. From these calculations, we can identify the correlation of how much clearance Effect has on the EGT Margin deterioration. From the calculation, the decrease in EGT Margin value on HPT is 7.4332 °C and the decrease in EGT Margin value on HPC is 7.792785 °C with a total decrease in EGT Margin value due to clearance on HPC and HPT is 15.225985 °C or contributes 58.1 % of the decrease in the value of EGT Margin since the last mesin repair.